Diagnósticos dermatológicos em recém-nascidos pré-termo: estudo transversal - Danielle Arake Zanatta; Carine Andrade Celeira Lima; Jessica Castro da Silva; Vânia Oliveira de Carvalho (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVE: To determine the frequency of dermatological diagnoses in preterm newborns and the associated perinatal factors. METHODS: This is a cross-sectional analytical study with a convenience sample and prospective data collection, carried out between November 2017 and May 2018. Were examined 151 premature and late preterm neonates admitted to the neonatal intensive care unit in a hospital of tertiary care level. The studied population was evaluated to evidence, describe and photograph the dermatological diagnoses present up to 28 days of life. RESULTS: The frequency of dermatological diagnoses was 99.3%, being the most observed: lanugo in 128 newborns (84.7%), salmon spot in 115 (76.1%), sebaceous hyperplasia in 89 (58. 9%), physiological flaking in 74 (49%), mongolian stain in 54 (35.7%), Epsteins pearl in 43 (28.4%), traumatic skin lesions in 42 (27.8%), milia cyst in 40 (26.4%), jaundice in 36 (23.8%) and toxic erythema in 20 (13.2%). Participants with a higher gestational age had a higher frequency of salmon spot, toxic erythema, mongolian spot, sebaceous hyperplasia, milia cyst and Epsteins pearl. CONCLUSION: Dermatological diagnoses were frequent and those of older gestational age had a higher frequency of physiological changes and birthmarks. Traumatic skin lesions were among the 10 most frequently observed, reinforcing the need to implement protocols for neonatal skin care, with emphasis on premature infants.